Academic Storage Cluster - Von Tottleben, Alexander; Ihle, Cornelius; Schubotz, Moritz; Gipp, Bela (2021 ACM/IEEE Joint Conference on Digital Libraries (JCDL), 2021)
Decentralized storage is still rarely used in an academic and educational environment, although it offers better availability than conventional systems. It still happens that data is not available at a certain time due to heavy load or maintenance on university servers. A decentralized solution can help keep the data available and distribute the load among several peers. In our experiment, we created a cluster of containers in Docker to evaluate a private IPFS cluster for an academic data store focusing on availability, GET/PUT performance, and storage needs. As sample data, we used PDF files to analyze the data transport in our peer-to-peer network with Wireshark. We found that a bandwidth of at least 100 kbit/s is required for IPFS to function but recommend at least 1000 kbit/s for smooth operation. Also, the hard disk and memory size should be adapted to the data. Other limiting factors such as CPU power and delay in the internet connection did not affect the operation of the IPFS cluster.